2022
DOI: 10.1088/1741-2552/ac5757
|View full text |Cite
|
Sign up to set email alerts
|

Corticomuscular integrated representation of voluntary motor effort in robotic control for wrist-hand rehabilitation after stroke

Abstract: Objective: The central-to-peripheral voluntary motor effort (VME) in physical practice of the paretic limb is a dominant force for driving functional neuroplasticity on motor restoration post-stroke. However, current rehabilitation robots isolated the central and peripheral involvements in the control design, resulting in limited rehabilitation effectiveness. The purpose of this study was to design a corticomuscular coherence (CMC) and electromyography (EMG)-driven (CMC-EMG-driven) system with central-and-peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 57 publications
1
30
1
Order By: Relevance
“…Meanwhile almost no false negative detections were obtained. The classification accuracy achieved in the present work is higher than that reported in the two available studies using CMC for online control of robotic orthosis in a rehabilitation context ( Chowdhury et al, 2019 ; Guo et al, 2022 ). Comparable performances were obtained in Chowdhury et al (2019) when an approach based on statistical correlation is used instead of the classical CMC algorithm.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Meanwhile almost no false negative detections were obtained. The classification accuracy achieved in the present work is higher than that reported in the two available studies using CMC for online control of robotic orthosis in a rehabilitation context ( Chowdhury et al, 2019 ; Guo et al, 2022 ). Comparable performances were obtained in Chowdhury et al (2019) when an approach based on statistical correlation is used instead of the classical CMC algorithm.…”
Section: Discussioncontrasting
confidence: 74%
“…Regarding the timing achieved in the classification decision with the parameters selected by this analysis, CMC features were able to provide a fast classification in stroke patients which ensures not only to exploit and train central-to-peripheral communication ( Guo et al, 2022 ), but also to send ecological feedback to the patient right after the onset of the movement attempt (a feedback that is congruent in timing and content with the exercise setting), favoring an effective motor re-learning. Comparing classification speed with previous works on rehabilitative BCIs during movement attempts, we obtained comparable ( Mrachacz-Kersting and Aliakbaryhosseinabadi, 2018 ) or better ( Biasiucci et al, 2018 , 3.5–5 s to deliver feedback) results with respect to EEG-based approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the understanding of basic mechanisms related to stroke recovery, it has been a trend to combine different types of neurorehabilitation techniques. Based on the differences in strategies of robotic control, it has been divided into the central-intention-driven and peripheral-effort-driven paradigms [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…They found that bilateral cortical activation was prevalent in both motor tasks, with higher activation in the contralateral compared to the ipsilateral primary motor cortex (Yang et al, 2020). Laterality index (LI) was often used to quantify the phenomenon of hemispheric asymmetry and for understanding 10.3389/fnins.2022.935827 interhemispheric patterns of action and functional changes in the brain (Belfatto et al, 2018;Lemée et al, 2020;Guo et al, 2022). Delorme used the LI to the assess changes in the hemispheric balance between cortical sensorimotor areas in stroke patients (Delorme et al, 2019).…”
Section: Introductionmentioning
confidence: 99%